DISAIN CONVERTER KITS MODIFIKASI SISTEM BAHAN BAKAR MOTOR BENSIN MENJADI BERBAHAN BAKAR GAS - Achmad Fauzan HS (Jurnal Gamma, 2009)
In an effort to suppress the release of methane gas from garbage to atmostfir which contributingto the greenhouse effect and global warming then conducted too studies for methane gas captureand methane gas to use for the purposes of this engine with a converter kit. This research is dedicatedto obtain a set of tools used to convert gasoline into motor fuel gas. The study of several possiblemodels of fuel gas distribution, is applied by maintaining fuel consumption of gasoline (hybrid).Outcome to design a set of tools used to convert gasoline motor fuel gas into the form ofdrawings, specifications of equipment and components, work systems, prototypes and guidelines.